Genome-wide identification of the geranylgeranyl pyrophosphate synthase (GGPS) gene family involved in chlorophyll synthesis in cotton - Wenxiang Feng; Teame Gereziher Mehari; Hui Fang; Meijun Ji; Zijian Qu; Mengxue Jia; Dongmei Wang; Allah Ditta; Muhammad Kashif Riaz Khan; Yunying Cao; Jianyong Wu; Baohua Wang (2023)
Geranylgeranyl pyrophosphate synthase (GGPS) is a structural enzyme of the terpene biosynthesis pathway that is involved in regulating plant photosynthesis, growth and development, but this gene family has not been systematically studied in cotton.In the current research, genome-wide identification was performed, and a total of 75 GGPS family members were found in four cotton species, Gossypium hirsutum, Gossypium barbadense, Gossypium arboreum and Gossypium raimondii. The GGPS genes were divided into three subgroups by evolutionary analysis. Subcellular localization prediction showed that they were mainly located in chloroplasts and plastids. The closely related GGPS contains a similar gene structure and conserved motif, but some genes are quite different, resulting in functional differentiation. Chromosome location analysis, collinearity and selection pressure analysis showed that many fragment duplication events occurred in GGPS genes. Three-dimensional structure analysis and conservative sequence analysis showed that the members of the GGPS family contained a large number of α-helices and random crimps, and all contained two aspartic acid-rich domains, DDxxxxD and DDxxD (x is an arbitrary amino acid), suggesting its key role in function. Cis-regulatory element analysis showed that cotton GGPS may be involved in light response, abiotic stress and other processes. A GGPS gene was silenced successfully by virus-induced gene silencing (VIGS), and it was found that the chlorophyll content in cotton leaves decreased significantly, suggesting that the gene plays an important role in plant photosynthesis.In total, 75 genes were identified in four Gossypium species by a series of bioinformatics analysis. Gene silencing from GGPS members of G. hirsutum revealed that GGPS plays an important regulatory role in photosynthesis. This study provides a theoretical basis for the biological function of GGPS in cotton growth and development.